Khandan - Bhimsingh, A.; Vasu, Ravi; Ravi; Rajendra Kishan; Moser Baer (New Delhi, India) (New Delhi : Moser Baer Entertainment, 2010)
After the passing of Ramswaroop Lal, his two sons, Jeevandas and Shankar take over the control of their farmland. Jeevandas marries Bhagvanti and has no children, while Shankar marries Parvati and has two sons, Govind and Shyam. Due to an accident with an electric pole, Govind's right side gets paralyzed. Years later, Shyam has gone for further studies to the big city, while the only relatives of Bhagvanti, Navrangi Lal and his sister, Neelima, have moved in with the Lal family. When Shyam returns, he falls in love with Neelima, and then begin a series of misunderstandings and disagreements which result in the house being divided in two - with Jeevandas, Bhagvanti, Shyam, Navrangi, and Neelima on one side, and Govind, his wife, Radha, Shankar, and Parvati on the other. Navrangi borrows money from Bhagvanti and invests it in a Carnival, however, most of his earnings are stolen by two dancers...
Copyright notice on container: Moser baer
Originally released theatrically in 1965.
Summary taken from IMDB.com.
Music ; Ravi
Sunil Dutt, Nutan, Helan and Pran
NTSC all region
Keywords: Family -- Drama; Musical -- Drama